Single-Conidium Encapsulation in Oil-in-Water Pickering Emulsions at High Encapsulation Yield - Kotliarevski, Liliya; Mani, Karthik Ananth; Feldbaum, Reut Amar; Yaakov, Noga; Belausov, Eduard; Zelinger, Einat; Ment, Dana; Mechrez, Guy (Frontiers in Chemistry, 2021)
This study presents an individual encapsulation of fungal conidia in an oil in water Pickering emulsion at relatively single conidium encapsulation yield reaching to 44%. The single conidium encapsulation yield was characterized via analysis of confocal microscopy micrographs. Mineral oil-in-water emulsions stabilized by amine-functionalized titania dioxide (TiO2-NH2 or titania-NH2) particles were prepared. The structure and the stability of the emulsions were investigated at different compositions by confocal microscopy and LUMiSizer® respectively. The most stable emulsions with a droplet size suitable for single-conidium encapsulation were further studied for their individual encapsulation capabilities. The yields of individual encapsulation in the emulsions; i.e., the number of conidia that were individually encapsulated out of the total number of conidia, were characterized by confocal microscopy based assay. This rapid, easy to use approach to single-conidium encapsulation, which generates a significantly high yield with eco-friendly titania-based emulsions, only requires commonly used emulsification and agitation methods.